FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PEKERJA PROYEK PEMBANGUNAN JALAN TOL CINERE - JAGORAWI SEKSI 3 PT. PP PRESISI TBK - Aulia Salwadina, (2023)
A project acceleration is performed to overcome delayed projects in Section 3 of the Cinere-Jagorawi Toll Road construction. This condition may cause an increase in work demands and working hours, which may lead to poor workers' performance. This study aims to determine factors related to poor workers' performance at the Cinere-Jagorawi Toll Road construction project Section 3 PT. PP Presisi Tbk. This research is a quantitive study using a cross-sectional design. The number of samples was determined using a total sampling technique with 90 workers as respondents. The instrument used to collect primary data is a questionnaire sheet. Data analysis performed was univariate analysis, bivariate analysis using the Chi-square test, and multivariate analysis using the predictive model logistic regression test. The results of the multivariate analysis showed that safety culture, work motivation, and hydration status are related to worker performance, with work motivation [POR = 5.828 (95% CI; 2.193-15.492)] as the most dominant variable. Thus, it is highly recommended that all workers should be able to maintain self-motivation, be accustomed to safety culture, minimize and report delinquency at work, and continue consuming sufficient mineral water to maintain work performance status.